The Influence of Consciousness on Inhibition of and Attentional Bias to Stimuli Associated with Drugs among Heroin Users - V Nejati; A Sadeghi Meresht; Y Moradi; B Barzegar (Drug Control Headquarters, Research and Education Office, 2014)
Objectives: This study aimed to examine the effect of consciousness on inhibition of and attentional bias to stimuli associated with drugs among heroin users and their counterparts. Method: In this study, a causal-comparative research method was used. All persons dependent on opiates in Abhar city constituted the study population. The number of 120 participants containing two 60-person groups of heroin users and their counterparts (i.e. non-users) were selected through convenience sampling. The two groups had been matched for age and sex and were compared through conducting the two neurological tests of Dot Probe and Stroop tests. Findings: The results showed that there was a difference between the two groups on Dot Probe test where the normal group outperformed the other one. In Stroop test, drug stimuli are provided either consciously or unconsciously, identified then, the stimuli in drug users are decided upon. Conclusion: Given the devastating effects of addiction on cognitive ability, cognitive problems should be addressed in treating patients.